KEWENANGAN NOTARIS DALAM MEMBUAT AKTA OTENTIK AKAD PEMBIAYAAN MUDHARABAH BERDASARKAN HUKUM ISLAM - Ahmad Febry (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2015)
Abstract : Indonesian economic Islam system has been well known by published The Statute Number 21 on 2008 about Syariat Banks. During on its doing of banking enrole -- the contract between credditure and debiture like mudharabah lease act â€“ must need the notary justify as authentical act for legal security the whole parties. This research patternized about the notaryâ€™s enrole on making its authentical act of mudharabah lease based on Islamic law contract, the comparison acts between KUH Perdata and Islamic law contract, and the notary opportunity by making its mudharabah lease contract at Islamic banking practice. This research is normative based on legal security theory, law connectivity theory, and maslahat theory. This research use legal prime, secunder, tersier, and conceptual approach, historical approach, statute approach, and comparative approach methods. The final conclusion on this research is that the notary justify as authentical act of mudharabah lease based on Islamic law written in Al-Quran Al-Baqarah 282. The comparison act between KUH Perdata and Islamic law is the similarity of its established contract, the legal of conditional act, the freedom of contract, and the consensus principle. Then the notary opportunity by making its mudharabah lease contract at Islamic practical banks has many opportunities that can be measured by industrical activity growth and Islamic economical principle. Keywords : Notary, Authentical Minute, Mudharabah Lease Contract.